Intravenous self‐administration of benzydamine, a non‐steroidal anti‐inflammatory drug with a central cannabinoidergic mechanism of action. (21st April 2017) - Avvisati, Riccardo; Meringolo, Maria; Stendardo, Emiliana; Malavasi, Elisa; Marinelli, Silvia; Badiani, Aldo
Abstract: Benzydamine (BZY) is a non‐steroidal anti‐inflammatory drug used for the topical treatment of inflammations of the oral and vaginal mucosae. Virtually nothing is known about the central pharmacological actions of BZY. Yet there are reports of voluntary systemic overdosage of BZY in drug addicts, resulting in a euphoric, hallucinatory state. In the present study, we investigated the reinforcing properties of BZY in a rat self‐administration paradigm. We found that BZY has a powerful reinforcing effect and that this effect is greatly facilitated in animals that already had substance experience, having previously self‐administered heroin and cocaine, indicating cross sensitization between BZY and other common drugs of abuse. We then assessed the effect of BZY on prelimbic cortex‐to‐nucleus accumbens glutamatergic transmission, using field recordings in rat parasagittal brain slices. BZY dose‐dependently reduced both field excitatory post synaptic potential amplitude and paired pulse ratio, suggesting a presynaptic mechanism of action. Similarly to the in vivo paradigm, also the electrophysiological effects of BZY were potentiated in slices from animals that had undergone cocaine and heroin self‐administration. Furthermore, BZY‐induced Long Term Depression (LTD)‐like responses in the prelimbic cortex‐to‐nucleus accumbens circuitry were significantly reduced in the presence of the CB1 receptor antagonist AM251. These findings provide firm evidence of the abuse liability of BZY and suggest a possible cannabinoidergic mechanism of action. Further research is needed in order to give insights into the molecular mechanism underlying BZY psychoactive and reinforcing effects, to better understand its abuse potential. Abstract : Abuse of the anti‐inflammatory drug benzydamine (BZY) has been reported, especially in drug addicts, but experimental evidence is lacking. We report here that BZY (1) has powerful reinforcing effects in the rat and these effects are facilitated by previous exposure to cocaine and heroin and (2) induces long‐term depression of cortico‐accumbens synaptic transmission, a phenomenon partially blocked by CB1 receptor antagonism. Our findings provide firm evidence of the addictive potential of BZY and suggest a cannabinoidergic mechanism of action.